Cycling efficiency and pedalling frequency in road cyclists - Chavarren, J.; Calbet, J. A. (European Journal of Applied Physiology, 1999)
The results may help us to understand why competitive cyclists often pedal at cadences of 90-105 rpm to sustain a high power output during prolonged exercise.